ANALISIS PENGARUH KARAKTERISTIK DISTRIBUTOR, DUKUNGAN PERUSAHAAN DAN ORGANISASI PEMBELAJARAN TERHADAP KINERJA DISTRIBUTOR MULTI LEVEL MARKETING (MLM) - Aqmala, Diana (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2011)
Salesperson plays an important role for the survival of the company. The roleof salespeople in the Multi Level Marketing company is a distributor, which will promoteproducts and business plan. Distributor is very important because of the high competition between companies who also want to increase product sales. The key of success in MLM companies depends on how the company is able to improve the performance of distributors.Problem of this research is how the characteristic Distributors, companies support and organization learning affect the performance of MLM distributors. Sampling technique used was purposive sampling method that used as many as 50 people Tianshi distributors in Semarang.The results of data analysis showed that there is significant influence between the characteristic distributors, companies support and Organization Learning to the performance MLM distributor.